2019
DOI: 10.2196/14976
|View full text |Cite
|
Sign up to set email alerts
|

Growing Disparities in Patient-Provider Messaging: Trend Analysis Before and After Supportive Policy

Abstract: BackgroundPublic policy introduced since 2011 has supported provider adoption of electronic medical records (EMRs) and patient-provider messaging, primarily through financial incentives. It is unclear how disparities in patients’ use of incentivized electronic health (eHealth) tools, like patient-provider messaging, have changed over time relative to disparities in use of eHealth tools that were not directly incentivized.ObjectiveThis study examines trends in eHealth disparities before and after the introducti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Future research could specifically focus on a health care region, integrate Loop with existing eHealth tools, pilot a compensation structure for asynchronous communication, deimplement or re-design optimal communication workflows from the ground up, and support requirements or conditions for collaboration to occur. In addition, future research should examine the impact of eHealth implementation on health disparities, which have been shown to increase with the introduction of patient–provider messaging tools [ 66 ]. Despite the considerable and seemingly intractable barriers identified in this study, the trend toward more digital communication in health care is inevitable and it is likely that an interoperable system of communication and documentation will emerge in time.…”
Section: Discussionmentioning
confidence: 99%
“…Future research could specifically focus on a health care region, integrate Loop with existing eHealth tools, pilot a compensation structure for asynchronous communication, deimplement or re-design optimal communication workflows from the ground up, and support requirements or conditions for collaboration to occur. In addition, future research should examine the impact of eHealth implementation on health disparities, which have been shown to increase with the introduction of patient–provider messaging tools [ 66 ]. Despite the considerable and seemingly intractable barriers identified in this study, the trend toward more digital communication in health care is inevitable and it is likely that an interoperable system of communication and documentation will emerge in time.…”
Section: Discussionmentioning
confidence: 99%
“…Among older adults, its prevalence rose from 2.7% in 2009 to 14.2% in 2018 [8]. Regardless of increasing trends, email PPC remains underutilized, and disparities exist based on demographic, socioeconomic, and health-related characteristics [7,[9][10][11][12]. Previous studies have found that adults who engage in email PPC are more likely to be female and younger aged; living in urban areas; have higher levels of education and income; and have a history of chronic disease [7,[9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of increasing trends, email PPC remains underutilized, and disparities exist based on demographic, socioeconomic, and health-related characteristics [7,[9][10][11][12]. Previous studies have found that adults who engage in email PPC are more likely to be female and younger aged; living in urban areas; have higher levels of education and income; and have a history of chronic disease [7,[9][10][11]. Several studies have found that non-Hispanic White adults are more likely to use email PPC than non-Hispanic Black and Hispanic adults [4], yet the usage of email PCC among Hispanic adults varies by US-and foreign-born subgroups [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…53 Non-users are significantly more likely to be male, Black, have Hispanic ethnicity, have lower education attainment, and have lower income. [54][55][56][57] However, our review of literature illustrates that reasons for these disparities have not been well-established in the setting of breast cancer.…”
Section: Accepted Manuscriptmentioning
confidence: 92%